Retailing Management / Sixth Edition - Davidson William R; Stampfl Ronald W; Sweeney Daniel J (John Wiley & Sons, Ltd, 1988)
Foundations for Retailing Management: Understanding the External Environment, Retailing Management and Strategy, Creating Internal Environments, Merchandise Management, Operations and Human Resources Management, Review and Prospect, Cases, Appendixes, Bibliography, Index.
Foundations for Retailing Management: Understanding the External Environment, Retailing Management and Strategy, Creating Internal Environments, Merchandise Management, Operations and Human Resources Management, Review and Prospect, Cases, Appendixes, Bibliography, Index.